MEDB-38. Significance of CSF cytology and neurologic deterioration in relapsed medulloblastomas in the German HIT-REZ-97/-2005 Studies and the HIT-REZ-Register. (3rd June 2022) - Tschirner, Sebastian; Adolph, Jonas E; Gaab, Christine; Tippelt, Stephan; Mikasch, Ruth; Mynarek, Martin; Rutkowski, Stefan; Pietsch, Thorsten; Bison, Brigitte; Warmuth-Metz, Monika; Pfister, Stefan M; Milde, Till; et al.
Abstract: BACKGROUND: Follow-up examinations are an essential part of the aftercare of patients with brain tumours. We investigated survival in relation to neurological impairment and positive CSF findings at first relapse/progression of medulloblastomas. METHODS: We collected data from patients with relapsed medulloblastoma from the German HIT-REZ studies (HIT-REZ-1997, HIT-REZ-2005, HIT-REZ-Register, n=342). Survival differences dependent on tumour cell-positive and -negative CSF cytology as well as on new onset or worsening of neurological impairment (i.e. headache, nausea/vomiting, ataxia, seizures and others) were analysed. RESULTS: 247 patients with a recurrent medulloblastoma were evaluable for CSF cytology at first relapse/progression (positive n=97, negative n=150). Patients with tumour cell-positive CSF results showed a significantly shorter median PFS and OS time compared to patients with negative CSF cytology [PFS: 9.1 (CI: 5.3-12.9) vs. 16.8 (CI: 13.8-19.8) months, plog rank test=0.001; OS: 14.4 (CI: 12.3-16.4) vs. 41.8 (CI: 33.3–50.4) months, plog rank test<0.001]. The shortest PFS and OS were observed in SHH-activated (n=18) and group 3 medulloblastomas (n=23) independently of CSF cytology result [median PFSSHH: 4.3 (CI:1.1-12.2), OSSHH: 6.3 (CI:1.1-18.7); PFSgroup3: 4.2 (CI:2.3-13.1), OSgroup3: 13.2 (CI:7.1-18.5) months]. For analysis of the impact of neurological deterioration on survival at first relapse, 249 Patients were evaluable. 105 patients with new or severely worsened neurological impairment at first relapse/progression displayed a significantly poorer PFS and OS time in comparison to 144 patients with unchanged or improved neurological symptoms [PFS: 8.2 (CI: 6.0-10.3) vs. 14.9 (CI: 12.0-17.9) months, plog rank test=0.001; OS: 15.1 (CI: 9.5-20.6) vs. 32.6 (CI: 26.2-38.4) months, plog rank test<0.001]. CONCLUSIONS: Patients with relapsed medulloblastoma show significantly worse survival (PFS and OS) in presence of positive CSF cytology or neurologic deterioration at relapse. These findings could be relevant for patient/parents counselling and treatment recommendations at relapse. Funded by the German Children Cancer Foundation